ANALISIS BEBERAPA VARIABEL YANG MEMPENGARUHI PROFITABILITAS PADA PERUSAHAAN MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Tohir Tohir; Ade Banani (Performance: Jurnal Personalia, Financial, Operasional, Marketing dan Sistem Informasi, 2012)
The research that entitled “Analisis Beberapa Variabel yang Mempengaruhi Profitabilitas pada Perusahaan Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia” is a case study that aims to acknowledge and analyze whether there is influence of the size of companies, debt equity ratio (DER), the growth of profits, and sales of profitability. Then, it will also analyze the variables affecting the profitability of the company among size, debt equity ratio, the growth of profits, and sales. Sampling method used in this research is the purposive sampling method, consisting 14 sample food and beverage companies listed on the Indonesia stock exchange. Using multiple regression analysis, t test, and F test in testing, both simultaneously and partially, and the elasticity test to find out which the independent variables having the greatest impact, it can be inferred that there is significance influence from debt to equity ratio (DER), the growth of profits, and sales of profitability. Next, the sale is the independent variable that has the greatest influence on profitability. Therefore, the company should pay more attention to the sales policy. The increased sales may be as consideration for investors to be able to invest in the company.